C.M. Woolgar: The Culture of Food in England 1200–1500 - Dalby, Andrew (Petits Propos Culinaires, 2016)
C.M. Woolgar: The Culture of Food in England 1200–1500: Yale University Press, 2016: 356 pp., hardback, £30.00.